Analisis Komprehensif Kesehatan Keuangan Sektor Pariwisatan dan Transportasi dengan Menggunakan - Nur Fitriyah; Bambang Bambang; Yusli Mariadi (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
This study aims to analyze and compare the financial condition of tourism and transportation sector companies listed on the Indonesia Stock Exchange before and during COVID-19 using the Altman, Springate, Zmijewski, and Grover models. The type of research used is comparative descriptive research. This comparative study aims to compare the financial health of the tourism and aviation sectors before and during COVID-19. The source of data in this study was obtained from the IDX website, namely http://www.idx.co.id. Data analysis using the Z Score method Altman, Springate, Zmijewski and Grover to determine the financial condition then perform individual and comparative analysis. The results of the study stated that using the four Z-score methods Altman, Springate, Zmijewski, and Grover, the financial condition of the transportation and tourism sectors had decreased financial health since the onset of COVID-19. Where the tourism and transportation sectors before the Covid-19 outbreak were on average safe but after the Covid-19 the level of distress experienced an increase and their safe position decreased. This is because during the Covid-19 period there was a government policy to limit travel and crowds in the community. Where the government implements PSBB policies, transitional PSBB, emergency PPKM to four-level PPKM so that people do not dare to travel and this has a huge impact on the transportation and tourism sectors